O-194 Prevalence of workplace violence amongst healthcare workers: estimates from a before-after study on incident reporting in Northern Italy. (14th March 2023) - Veronesi, Giovanni; Giusti, EM; Borchini, R; Ghelli, M; Banfi, A; Luoni, A; Persechino, B; Di Tecco, C; Ronchetti, M; Gianfagna, F; De Matteis, S; Ferrario, MM
Abstract : Introduction: Prevalence estimates on workplace violence (WV) in healthcare workers (HCWs) in Italy range between 36% and 98%, but are mostly limited to studies on high-risk subpopulations and subject to participation bias. Hospital incident reporting registers cover the entire HCW population, but suffer from known underreporting. The DeVOS study implemented a new reporting procedure in two large (n=9037 HCW) general hospitals in Lombardia (Northern Italy), effective from Nov, 1st, 2021. We aimed to compare violence prevalence estimates on HCWs before and after the new procedure's implementation. Material and Methods: In the before period (2015–2020), notification procedures were hospital-based and not specific for WV. We introduced a simplified, regional guidelines-compliant WV reporting, which was explained to the work force coordinators; and a web-based data collection platform. Underreporting was estimated as the observed to expected WV ratio (from literature). WV prevalence was estimated on the number of HCWs, in the after period disentangling the contribution of first reports from recurrences on the same worker. Results: In the 6-year before period, the observed to expected WV ratio was 0.54 (95%CI:0.48–0.62), ranging from 0.32 to 0.87 in the two hospitals. Victim's demographic/job title information was not reported in most of the reports. WV prevalence declined in one hospital (2015=1.68%, 2020=0.30%), and raised in the other (2015=0.2%, 2020=1.0%). In the 12-month after period, the HCW reported 170 WV, 80% more than expected based on the before prevalence. Data completeness was above 97%. WV prevalence was 1.80% (95%CI:1.55%-2.10%); of this, 1.47% and 0.33% was due to first and recurrent aggressions, respectively. Among the HCWs, young (3.33%), nurses (3.06%) and men (2.44%) reported the highest prevalence. Psychiatric wards and emergency-urgency departments reported the highest WV prevalence. Conclusions: A guidelines-compliant incident reporting system reduces workplace violence underreporting in HCWs, possibly allowing more accurate prevalence estimates to inform prevention strategies.